Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1517/14740338.2016.1130126
|View full text |Cite|
|
Sign up to set email alerts
|

The safety and efficacy of Avanafil, a new 2ndgeneration PDE5i: comprehensive review and meta-analysis

Abstract: Areas covered: All placebo-controlled randomized clinical trials (RCTs) on the effect of avanafil in patients with ED were reviewed and meta-analyzed. So far, 5 different RCTs on avanafil have been published, including 1379 and 605 patients in active and placebo groups, respectively. Avanafil was up to 3-fold superior to placebo in determining successful sexual intercourse. Although head-to-head comparative studies are still lacking, re-analyses of available data, showed that avanafil had comparable efficacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 58 publications
(99 reference statements)
1
57
0
2
Order By: Relevance
“…Although not life threatening, these adverse events can be extremely bothersome and contribute to PDE5i discontinuation, but the present data suggest that the contribution of side effects is similar to other determinants in favoring PDE5i dropout. It is interesting to note that second generation of PDE5i (avanafil) demonstrates similar efficacy despite lower side effects when compared to the first generation of PDE5i (Corona et al ., b). However, data on avanafil dropout are not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…Although not life threatening, these adverse events can be extremely bothersome and contribute to PDE5i discontinuation, but the present data suggest that the contribution of side effects is similar to other determinants in favoring PDE5i dropout. It is interesting to note that second generation of PDE5i (avanafil) demonstrates similar efficacy despite lower side effects when compared to the first generation of PDE5i (Corona et al ., b). However, data on avanafil dropout are not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis investigates the effect of intervention with any physical activity on ED patients in randomized controlled trails, having, as an end-point, variation in ED scoring, as evaluated through the International Index of Erectile Function erectile function domain (IIEF-EFD). They found that on average physical activity increased IIEF-EFD by almost 4 points, an effect that is not very far from the 5 point increase -as evaluated in the meta-analysis -by the most recent phos-phodiesterase type 5 inhibitor (PDE5i) on the market, avanafil [59].…”
Section: Effect Of Lifestyle Change On Sexual Symptomsmentioning
confidence: 91%
“…[ 20 , 21 ] Although meta-analyses have shown that PDE5 inhibitors can safely and effectively treat ED, whether they are still safe and effective for DMED with more complex etiologies remains to be assessed. [ 22 , 23 ] Therefore, this review hopes evaluate the efficacy and safety of PDE5 inhibitors in the treatment of DMED to provide the newest evidence for clinical.…”
Section: Introductionmentioning
confidence: 99%